Learning versus Stealing How Important are Market-Share: Reallocations to India's Productivity Growth? - Harrison, Ann E. (The World Bank, 2011)
Recent trade theory emphasizes the role of market-share reallocations across firms ("stealing") in driving productivity growth, while the older literature focused on average productivity improvements ("learning"). The authors use comprehensive, firm-level data from India's organized manufacturing sector to show that market-share reallocations did play an important role in aggregate productivity gains immediately following the start of India's trade reforms in 1991. However, aggregate productivity gains during the overall period from 1985 to 2004 were driven largely by improvements in average productivity, which can be attributed to India's trade liberalization and FDI reforms